Dinamika Ekonomi Ketenagakerjaan di Pedesaan pada Basis Agroekosistem Lahan Sawah Irigasi - Sugiarto Sugiarto (Politeknik Negeri Lampung., 2011)
Labor force dynamics will always change by job opportunity in agriculture sector and out side agriculture sector which change every time. The goal is this research is to show labor dynamics in micro in farming based of irrigation field. From the research which is comparing labor force in 2007 with 2010 showed performance of labor force participation in 2010 was higher than 2007. Such also with labor force education level in 2007 and 2010 same which is dominated by lower than 6 years education, but in 2010, the amount of labor force was increasing become upper than 10 years education. The development of labor force by source of livelihood in agriculture sector is 70 percent until 80 percent in 2007 becoming 50 percent until 60 percent. So that needs to develop job opportunity which have an industrial in agribusiness system to decrease the burden of labor force in agriculture sectors as job opportunity in villages Keywords: Dynamics of labor force in agriculture irrigation field